Effect of temperature and duration of immersion on the stability of prepared feeds in echinoculture. Issue 2 (3rd April 2021) - Secci, Marco; Ferranti, Maria Paola; Giglioli, Angelica; Pasquini, Viviana; Sicurelli, Doriana; Fanelli, Giovanni; Prato, Ermelinda
ABSTRACT: The aim of this study was to provide new insights into the stability in water of the prepared feeds for echinoculture. The stability tests of four prepared feeds were carried out in laboratory in two different trials corresponding to different temperature levels (24°C and 19°C) and four different times of immersion (up to 72 h). Temperature and duration of immersion significantly affected the stability of feeds. Feed 1 was the most stable whereas Feed 3 was the least stable feed, as it started to dissolve in a few hours. Feed 2 and Feed 4 remained stable at 19°C all along the trial, whereas at 24°C remained intact for only 30 h. To optimize the echinoculture practice at temperature >19°C, we recommend a feeding regime at least 3 times a week, whereas at lower temperature we suggest an intermittent feeding regime.